Comparative Study on the Physicochemical and Sensory Attributes of Okoho Root (Cissus Populnea) and the Two Varieties of Ogbono Seeds (Irvingia Gabonensis and Irvingia Wombolu) - Okakpu, Kasie; Ubbor, Stella; Okakpu, Chidiebere (Jurnal Bio-Geo Material Dan Energi, 2025)
This study investigated the physicochemical and sensory attributes of Okoho(Cissus populnea) and varieties of Ogbono seeds (Irvingia gabonensis and Irvingia wombolu). Okoho root and Ogbono seeds were processed into flours. The flours were used to formulate six samples which were analysed for functional properties, proximate composition, phytochemical composition and sensory attributes. The result of the functional properties of the flour samples showed that the value of the bulk density ranged from 0.65 to 0.95 g/ml, oil absorption capacity (9.23 to 10.53 g/ml), water absorption capacity (0.93 to 10.00 g/ml), swelling index (1.68 to 10.53 g/ml), foam capacity (0.98 to 11.76 g/ml), emulsion capacity (23.77 to 40.33 g/ml), wettability (0.46 to 7.37min/sec), viscosity (3.02 to 3.19 Pa.s ), gelation temperature (39.02 to 80.04 oC), and gelation time (0.43 to 2.30 min/sec. The result of the proximate composition showed that the moisture content ranged from 6.30 to 8.53%, crude protein (8.02 to 20.62%), crude fibre (2.04 to 20. 72%), ether extract (3.34 to 69.68%), ash (2.52 to 3.57%), and carbohydrate (10.24 to 43.65%). For phytochemical composition of the flour samples, the values of phytate ranged from 0.09 to 0.72%, oxalate (0.02 to 2.15%), phenol (0.11 to 10.27 mg/100g), saponin (0.61 to 2.72 mg/100g), steroid (0.01 to 6.16 mg/100g), tannin (0.25 to 1.67 mg/100g), alkaloid (0.87 to 1.72%), and flavonoid (1.16 to 4.87 mg/100g). The result of the sensory evaluation showed that the soup samples were generally acceptable by the consumers The result of this study showed that Okoho root contained the highest vital nutrient and could be used as a substitute for the costly and over-used Ogbono seeds.